Understanding Factors Affecting Investment Decisions: Financial Literacy - Hartono, Akhmad Salim; Prapanca, Detak (Universitas Muhammadiyah Sidoarjo, 2023)
This study explores the interplay between financial literacy, financial behavior, and employment status in relation to investment decisions. Conducted in Singopadu Village, Indonesia, the research employed a quantitative associative design with a sample of 100 participants selected through random sampling. Primary data was collected using questionnaires and analyzed using SPSS. The findings reveal significant influences of financial literacy, financial behavior, and employment status on investment decisions. The study emphasizes the importance of promoting financial literacy and cultivating positive financial behaviors to enhance investment choices, providing valuable insights for researchers and policymakers alike. Highlights: Financial literacy: Understanding the level of financial knowledge and awareness among individuals in Singopadu Village and its impact on investment decisions. Financial behavior: Examining the financial habits, practices, and attitudes of residents in Singopadu Village and how they influence investment choices. Employment status: Investigating the relationship between employment status and investment decisions, considering factors such as income stability and job security. Keywords: Financial literacy, financial behavior, employment status, investment decisions, Singopadu Village.